Psychoneuroendocrine Nutritional Dermatology: The Interplay Between Diet, Psychological Stress, Cortisol, Sex Hormones, the Gut–Skin Axis, and Skin Health - Enkelejda Trebicka (Journal of Psychiatry and Psychological Sciences, 2026)
Nutritional dermatology has evolved into an interdisciplinary field that integrates nutrition, endocrinology, microbiome science, and psychological health. Emerging evidence demonstrates that dietary habits, chronic psychological stress, emotional well-being, and lifestyle behaviors influence skin physiology through psychoneuroendocrine and immunological pathways. In particular, the hypothalamic–pituitary–adrenal (HPA) axis, cortisol regulation, sex hormones, and gut microbiota have been identified as major mediators linking mental health and dermatologic outcomes. Objective This literature review aims to synthesize evidence published between 2015 and 2025 regarding the interactions among nutrition, psychological stress, hormonal regulation, the gut–skin axis, and skin aging, with a focus on psychodermatological mechanisms and potential lifestyle interventions. Methods A structured literature search was performed using PubMed, Scopus, and ScienceDirect databases. Eligible studies included systematic reviews, meta-analyses, randomized controlled trials, and observational studies investigating the relationship between nutrition, stress, cortisol, endocrine function, gut microbiota, and dermatologic outcomes. Results Evidence consistently demonstrates that chronic psychological stress and elevated cortisol impair epidermal barrier function, increase oxidative stress, alter sebaceous gland activity, and exacerbate inflammatory skin conditions including acne, psoriasis, atopic dermatitis, and rosacea. Dietary patterns characterized by high glycemic load and ultra-processed foods further amplify HPA-axis activation and systemic inflammation. Conversely, Mediterranean dietary patterns, omega-3 fatty acids, antioxidants, probiotics, regular physical activity, adequate sleep, mindfulness-based interventions, and stress-management strategies contribute to cortisol regulation, improved emotional well-being, reduced inflammation, and healthier skin aging trajectories. Emerging evidence also highlights the gut–brain–skin axis as a central psychoneuroimmunological pathway linking mental health and dermatologic disease. Conclusion Skin health should be viewed through an integrated psychoneuroendocrine framework in which nutrition, psychological stress, hormonal regulation, microbiome composition, and lifestyle behaviors interact dynamically. Future dermatologic interventions should incorporate nutritional counseling, stress-management approaches, and behavioral health strategies to optimize both mental well-being and dermatologic outcomes.